Teaching Benign Paroxysmal Positional Vertigo (BPPV): A Kinesthetic Model for Teaching the Dix-Hallpike and Canalith Repositioning Maneuvers - L. Renata Thronson (Association of American Medical Colleges, 2015)
Abstract In clinical practice, the diagnosis of benign paroxysmal positional vertigo (BPPV) is made by history and by the Dix-Hallpike maneuver. The condition is frequently treated in clinic with the canalith repositioning maneuver (CRM), which involves guiding a patient through a series of postures in order to reposition dislodged canaliths in the semicircular canal of the inner ear. While the Dix-Hallpike and CRM have been carefully described elsewhere, the model presented here is a novel three-dimensional, kinetic representation of the relevant anatomy. Uniquely, it can be used to practice the CRM, and it provides visual feedback to the learner, indicating clearly whether the maneuver is performed correctly. This teaching tool is a simplified, functional model of the posterior semicircular canal attached to a headband which, when worn by a simulated patient, helps the learner understand the relevant anatomy and pathophysiology of posterior canal BPPV. Attached to the model is a small ring representing a dislodged canalith which provides visual feedback to the learner as she guides her patient through the CRM. When the maneuver is performed correctly, the canalith slides to the appropriate position relative to the model of the semicircular canal. Learners practice in pairs, each taking a turn playing the patient and the clinician. This model has been used to teach the Dix-Hallpike and CRM to first-year internal medicine residents at the University of Washington. Practice with the model has been a popular element of an educational session on dizziness, itself part of a curricular series on core outpatient topics. This model has been presented to first-year internal medicine residents annually since 2012, and it is now part of the core classroom curriculum in ambulatory care in the University of Washington Medicine Residency Program. The 2013 cohort were asked to rate their comfort with the Dix-Hallpike and CRM on a scale of 1 = very uncomfortable to 5 = very comfortable. Forty residents completed pre− and postsession surveys. The mean rating improved from 1.87 prior to the session to 4.44 after.